Adolescents’ Experiences of Ecological Anxiety: A Qualitative Analysis of Two Cases - Čėnaitė, Neringa; Dervinytė-Bongarzoni, Asta (Psichologija, 2025)
People react to the ecological crisis with a range of emotions. The term ‘ecological anxiety’ is frequently mentioned in scientific literature, even though it lacks definition. It generally describes various forms of distress experienced in response to environmental degradation. In Lithuania, only a few scientific studies have so far explored the relationship between ecological crisis and mental health, and there is a particular lack of research on adolescents’ experiences and emotions regarding this issue. This qualitative analysis aims to ‘give voice’ to the experiences of two individuals of the late adolescence age period living in Lithuania who are anxious about ecological crisis. Participants respond to the crisis with a range of emotional and cognitive reactions, including feelings of guilt, helplessness, insecurity, low mood, and concentration issues. The ecological situation is closely related to their daily lives, plans, and relationships. The study’s findings align with tendencies observed in international research. This article could be helpful for mental health professionals working with adolescents and young people, as the prevalence of ecological anxiety is likely to increase, which means that more specialists will encounter this issue in their work.